2021
DOI: 10.1186/s13072-021-00394-8
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63 is a pioneer factor that binds inaccessible chromatin and elicits chromatin remodeling

Abstract: Background ΔNp63 is a master transcriptional regulator playing critical roles in epidermal development and other cellular processes. Recent studies suggest that ΔNp63 functions as a pioneer factor that can target its binding sites within inaccessible chromatin and induce chromatin remodeling. Methods In order to examine if ΔNp63 can bind to inaccessible chromatin and to determine if specific histone modifications are required for binding, we induce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 65 publications
4
22
0
Order By: Relevance
“…SFN was identified as a direct p53 and Np63 target that is FIGURE 2 | (A) p53 and Np63 can act as pioneer factors to evict/remodel nucleosomes and facilitate DNA accessibility, although other pioneer factors are likely responsible for nucleosome eviction at the majority of p53/ Np63 binding sites. (B) Certain nucleosome contexts, such as when the p53/p63 RE motif is near the nucleosome dyad, are recalcitrant to p53 and/or Np63 pioneer factor activity and remain unbound (Yu and Buck, 2019;Yu et al, 2021). (C) In epithelial cell types, p53 DNA binding can be facilitated by Np63 s pioneer factor activity, although specific biochemical mechanisms are still being fully elucidated.…”
Section: P53 and P63 -Dueling Rivals?mentioning
confidence: 99%
See 2 more Smart Citations
“…SFN was identified as a direct p53 and Np63 target that is FIGURE 2 | (A) p53 and Np63 can act as pioneer factors to evict/remodel nucleosomes and facilitate DNA accessibility, although other pioneer factors are likely responsible for nucleosome eviction at the majority of p53/ Np63 binding sites. (B) Certain nucleosome contexts, such as when the p53/p63 RE motif is near the nucleosome dyad, are recalcitrant to p53 and/or Np63 pioneer factor activity and remain unbound (Yu and Buck, 2019;Yu et al, 2021). (C) In epithelial cell types, p53 DNA binding can be facilitated by Np63 s pioneer factor activity, although specific biochemical mechanisms are still being fully elucidated.…”
Section: P53 and P63 -Dueling Rivals?mentioning
confidence: 99%
“…This rule is broken by pioneer transcription factors, which can bind to nucleosomal DNA either sequence-dependent or independent ( Zaret and Mango, 2016 ). Numerous recent studies suggest that the p53 family of transcription factors are pioneer transcription factors ( Sammons et al, 2015 ; Yu and Buck, 2019 ; Yu et al, 2021 ; Figure 2A ). Indeed, differential pioneer activity of p53 and p63 has the potential to explain some of the observed gene regulatory differences between these two siblings.…”
Section: Engaging Chromatin – the Pioneer Role Of The P53 Familymentioning
confidence: 99%
See 1 more Smart Citation
“…ΔNp63 is necessary to maintain basal cell identity and function; without ΔNp63, these cells downregulate basal markers, exit the cell cycle, and undergo a program of precocious differentiation into more committed epithelial cells of their resident tissue (Haas et al, 2019; Romano et al, 2012; Truong et al, 2006; Yang et al, 2018). While ΔNp63 exterts its control over basal cell identity directly by transcriptionally regulating expression of basal cell markers and functional components such as basement membrane-anchoring adhesion molecules (Carroll et al, 2006; Ferone et al, 2013; Ihrie et al, 2005; Kurata et al, 2004; Laurikkala et al, 2006; Romano et al, 2009), recent studies propose an epigenetic role for ΔNp63 as well, in which ΔNp63 cooperates with higher order chromatin remodelers and histone modifiers to rearrange the 3D topology and chromatin accessibility of the genome (Fan et al, 2018; Fessing et al, 2011; Mardaryev et al, 2014; Qu et al, 2019; Sethi et al, 2014), bookmark tissue-specific enhancer regions during differentiation (Kouwenhoven et al, 2015; Lin-Shiao et al, 2019), and acts as a pionner-like factor by binding and opening inaccessible chromatin (Fan et al, 2018; Santos-Pereira et al, 2019; Yu et al, 2021). With its multi-tiered influence over the fundamental basal cell program and critical role in virtually all epithelial tissue contexts in which its been studied, ΔNp63 serves as a promising target to modulate basal cell fate choice in regions of dysplastic remodeling within injured lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, incubation of Lola-I protein with nucleosome-bound sequences in vitro suggested that Lola-I preferentially binds to its motifs near the nucleosome edge when the DNA is partially unwrapped. Although there is no consensus on whether pioneer factors are defined by a certain binding mode in vitro (Klemm et al, 2019), such binding preference has previously been observed for some pioneer factors (Yu and Buck, 2019; Yu et al, 2021; Zhu et al 2018). Like for other pioneer factors, binding of Lola-I may lead to the recruitment of chromatin remodelers that remove the nucleosome (Judd et al, 2021; Zaret, 2020).…”
Section: Discussionmentioning
confidence: 99%